2021
DOI: 10.3390/microorganisms9102024
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Point Surveillance for Antimicrobial Resistance Profiles among Clinical Isolates of Gram-Negative Bacteria Recovered from Major Ha’il Hospitals, Saudi Arabia

Abstract: The devastating nosocomial resistance is an on-going global concern. Surveillance of resistance is crucial for efficient patient care. This study was aimed to conduct a surveillance in four major Ha’il Hospitals from September to December 2020. Using a multipoint program, records of 621 non-duplicate Gram-negative cultures were tested across 21 drugs belonging to different categories. Major species were Klebsiella pneumoniae (n = 187, 30%), E. coli (n = 151, 24.5%), Pseudomonas aeruginosa, (n = 84, 13.6%), Aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 71 publications
(77 reference statements)
2
18
1
Order By: Relevance
“…Strains isolated from sputum samples from ICU patients were sensitive to colistin. This observation is in line with a previous study conducted in the same region (Hail), which reported resistance of A. baumannii from COVID-19 and non-COVID-19 individuals to all antibiotics except colistin (5% resistance rate) and ertapenem [ 50 ]. Another study showed that A. baumannii isolated from endotracheal aspirate samples of nineteen COVID-19 patients was resistant to all tested antibiotics, except colistin with a resistance rate of 52% [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…Strains isolated from sputum samples from ICU patients were sensitive to colistin. This observation is in line with a previous study conducted in the same region (Hail), which reported resistance of A. baumannii from COVID-19 and non-COVID-19 individuals to all antibiotics except colistin (5% resistance rate) and ertapenem [ 50 ]. Another study showed that A. baumannii isolated from endotracheal aspirate samples of nineteen COVID-19 patients was resistant to all tested antibiotics, except colistin with a resistance rate of 52% [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are more dramatic than those reported in most of the studies [35][36][37][38], even though we have found some others with higher resistance rates [19,24,39]. For example, Kot et al identified all E. coli and P. mirabilis isolates as susceptible to carbapenems (vs. 99.1% and 91.1%, respectively, in our study), and an 84.4% susceptibility for K. pneumoniae isolates (vs. 68.4% sensitivity to ertapenem in ours) [17].…”
Section: Discussioncontrasting
confidence: 79%
“…To enhance the cationicity of MAF-1A, the analog Mt6 was designed and synthesized with the positively charged alkaline amino acid Lys substituted for the acidic amino acids Glu ( 5 , 12 , 19 , 24 ) and Asp ( 8 ). These substitutions increased the net charge of Mt6 from +2 (MAF-1A) to +9.…”
Section: Resultsmentioning
confidence: 99%
“… Acinetobacter baumannii is one of the multidrug-resistant pathogens that causes hospital-acquired infections. Numerous clinical studies are slowly revealing that it is difficult to cure A. baumannii infections due to its serious drug resistance and the side effects of anti- A. baumannii drugs ( 7 11 ). As a result, the World Health Organization has designated it as a top priority for novel antibiotic development ( 12 ).…”
mentioning
confidence: 99%